Nagrania dźwiękowe Ukraińców z obozów jenieckich w Niemczech podczas I wojny światowej w zbiorach Berliner Phonogramm-Archiv - Kołomyjeć, Olga (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2025)
This article presents the results of the first stage of research into newly acquired phonographic recordings collected among Ukrainian prisoners of war between 1915 and 1918 by participants in the Royal Prussian Phonographic Commission project, stored in the Berlin Phonogramm-Archiv. These recordings and accompanying archival documents were obtained and researched by the author of this article. The output of the contributors is considered in the context of the main principles of the foundational period of ethnomusicology in the first half of the 20th century and the significant contribution of German scholars to the development of scientific research on oral tradition music. The paper emphasises the importance of the studies in Germany of the founder of the Department of Musicology at the University of Lviv, A. Chybiński, according to the ideas of W. Humboldt University, which influenced his interdisciplinary approach in the process of building up the newly established department in the first decades of the 20th century, as well as Chybiński's personal diverse interests in musicology, including occasional research in the field of musical ethnography and his awareness of the importance of this area of study. The article draws a parallel between the formation of the programme of musicological studies at the Department of Musicology of Lviv University in the early twentieth century and the coexistence of various fields of study of musical art at the Department of Musicology of Ivan Franko National University, which was restored a century later.